Chalconas isoladas da myracrodruon urundeuva e 2-O-metilinositol isolado da magonia glabrata protegem neurônios de danos oxidativos e apoptose induzida por 6-hidroxidopamina (6-OHDA) : estudo em cultura primária de células mesencefálicas de ratos - Nobre Júnior, Hélio Vitoriano (2005)
The present work evaluated the cytoprotective effect of chalcone-enriched fraction (CEF) and 2-methyl-inositol (MIT) in primary rat mesencephalic cell culture exposed to the neurotoxin 6-hydroxydopamine (6-OHDA). The CEF was obtained from Myracrodruon urundeuva, a Brazilian medicinal plant used as an antiinflamatory and wound healing agent.in female genital tract. In this fraction there are the dimerics chalcones urundeuvinas A, B e C The other compound was the MIT isolated from Magonia glabrata, a plant popularly known as “Tingui de Bola”, which bark from its root is used as poison to catch the fishes from lakes and rivers. The immunohistochemical assay for tyrosine hydroxylase revealed that the percentage of dopaminergic cells in our cultures is approximately 2%. After exposition to 6-OHDA (40 and 200 microM) the cellular viability was reduced to 88,81% and 35,45% respectively. The mitochondrial activity was reduced to 88,8 and 35,4%, the nitrite levels was increased to 551,9% and 721,3% respectively and the lipid peroxidation was increased to 166,84% in the concentration of 200 microM, as observed in the MTT, nitrite and TBARS assays respectively. The results show that the exposition to CEF (100 microg/mL) before 6-OHDA (neuroprevention experiment) or after 6-OHDA (neurorescue experiment) reduced significantly the cell death caused by 6-OHDA (40 e 200 microM). The CEF prevented significantly the increase in nitrite levels induced by 6-OHDA (40 and 200 microM) (in both experiments), except in the neurorescue experiment in which the CEF failed to revert the increase in nitrite levels generated by 6-OHDA (200 microM). The CEF inhibited the lipid peroxidation induced by 6-OHDA (200 microM) in both experiments, and also showed antiapoptotic activity against 6-OHDA (40 and 200 microM) in both experiments. The MIT protected significantly TH- and TH+ cells from injury induced by 6-OHDA (40 and 200 microM) in both experiments. It showed a reduction in the nitrite levels generated by 6-OHDA in both experiments. The MIT also reverted the lipid peroxidation generated by 6-OHDA (200 microM) and showed antiapoptotic activity against 6-OHDA (40 and 200 microM) in both experiments. These results suggest that the neuroprotective action these compounds, CEF and MIT are due to antioxidant, besides a possible mitochondrial protection of these polyphenols. In related to MIT not must be discarded the idea of a second messenger action through the production of inositol triphosphate and protein kinase C activation. The findings may have a clinical importance in neurodegenerative conditions like Parkinson’s disease.